Mobilising the welfare machine: Questioning the resurgent socialist concern in China's Public Rental Housing Scheme. (4th November 2018) - Wang, June; Li, Mingye
Abstract : This study examined the resurgence of public housing provision in China since 2007 by situating it in a broad welfare regime analysis. Based on insights from Productivist Welfare Capitalism (Holliday, 2000. Productivist Welfare Capitalism, 706‒723) and Graduated Sovereignty (Ong, 2006a. Neoliberalism as exception ), we have sought to shed new light on the productivist approach through a study on Chinese cases. Using the examples of Chongqing and Nanjing, we argue in the study that the proactive action of the state to further commodify labour power has led to the flexible de‐articulation and re‐articulation of welfare and citizenship in an ongoing process of de‐territorialisation and re‐territorialisation of various segments of the population that own parcels of land. Another aspect of flexibility in the welfare regime is the double segmentation of population and territory, which is also contingent on, and subject to, alteration upon government decision.